2014
DOI: 10.1002/ejoc.201402850
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Indole‐Derived Allocolchicine Congeners through Pd‐Catalyzed Intramolecular C‐H Arylation Reaction

Abstract: The synthesis of several new heterocyclic structural analogs of the natural antimitotic agent allocolchicine is reported. As a key step an intramolecular Pd‐catalyzed C–H arylation reaction was used to close the seven‐membered ring fused with two electron‐rich aryl fragments. The stereostructure of the target compounds was determined by X‐ray crystal analysis. The primary biological assessment of the synthesized compounds was carried out on human lymphoma cells. Several allocolchicinoids were determined to pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 85 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…An intramolecular CH activation event at the C‐3 position was employed in the synthesis of indole‐based allocolchicine derivatives, described by the groups of Schmalz and Fedorov and co‐workers 105. Two slightly divergent methods were employed depending on the substituent on the N‐1 ring atom to afford the corresponding annulated indoles in good yields (Scheme ).…”
Section: Ch Activation At the C‐3 Position Of The Indole Frameworkmentioning
confidence: 99%
“…An intramolecular CH activation event at the C‐3 position was employed in the synthesis of indole‐based allocolchicine derivatives, described by the groups of Schmalz and Fedorov and co‐workers 105. Two slightly divergent methods were employed depending on the substituent on the N‐1 ring atom to afford the corresponding annulated indoles in good yields (Scheme ).…”
Section: Ch Activation At the C‐3 Position Of The Indole Frameworkmentioning
confidence: 99%
“…34 In 2009, Pieters and co-workers reported that compound 40 and its hydroiodide 39 were very active against Plasmodium falciparum (IC < 1 μM for 40), but were also very highly cytotoxic and exhibited low selectivity. 30 In 2014, Schmalz, Federov and co-workers 35 synthesized some indole-derived structural analogues of the natural antimitotic allocolchicine (41) ( Figure 6). 36 They used a reaction sequence in which the first step was a palladium-catalyzed intramolecular direct arylation of 3-(2′-iodo-3′,4′,5′trimethoxyphenyl)-1-(1′′-methyl-1H-indol-2′′-yl)propan-1-one (42) (Scheme 10).…”
Section: Methodsmentioning
confidence: 99%
“…36 They used a reaction sequence in which the first step was a palladium-catalyzed intramolecular direct arylation of 3-(2′-iodo-3′,4′,5′trimethoxyphenyl)-1-(1′′-methyl-1H-indol-2′′-yl)propan-1-one (42) (Scheme 10). 35…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This included a proliferation assay to determine cell concentrations and viability by using a CASI cell counter and apoptosis assays for nuclear DNA fragmentation quantified by FACS flow cytometric determination. For a full description of the methods involved in the preliminary evaluation of the compounds, see the supporting information of ref 7e. For details of the synergism experiments between 16da and vincristine on vincristine‐resistant cell lines, please refer to the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%